Japan : The Final Agony - Coox, Alvin (New York Ballantine Books, 1970)
FROM THE BACK COVER: "RAVAGED BY FIREBOMBS AND TORN BY HER EFFORTS TO PROVIDE THE MANPOWER, MUNITIONS AND FOOD TO MOUNT A SUFFICIENT FORCE TO REPULSE THE AMERICAN INVASION, WAR-WEARY JAPAN WAS DETERMINED STILL TO FIGHT-WITH BAMBOO SPEARS IN THE HANDS OF OLD MEN IF NECESSARY--BUT FINALLY HER LEADERS KNEW THE TRUTH: JAPAN HAD TO CAPITULATE OR
Includes Illustrations
Keywords: World War (1939-1945) -- Military Campaigns